2019
DOI: 10.2991/ijcis.d.190624.001
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Marketing Decision Support Systems for New Product Design: A Review

Abstract: A B S T R A C TProduct design is an important phase of the new product development process and one of the most crucial decisions in marketing. In the latest two decades, a significant number of marketing decision support systems (MDSSs) for automating new product design activities have been reported in the literature and have contributed to the evolution of knowledge in this area. Since the insights on what constitutes the design of new products are constantly evolving, it is unclear whether research on MDSSs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Theorem 2. Suppose w is an optimal control of AP strategies (8), and E is the solution to the corresponding model [41]. Then, there exists z such that…”
Section: A Necessary Condition For the Optimal Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Theorem 2. Suppose w is an optimal control of AP strategies (8), and E is the solution to the corresponding model [41]. Then, there exists z such that…”
Section: A Necessary Condition For the Optimal Controlmentioning
confidence: 99%
“…Based on the above discussions, Equations ( 2) and ( 10)-( 12) plus z(T) = 0 constitute the optimal system for the AP strategies (8). By using the well-known forward-backward Euler scheme in the optimal system, we get an optimal control of the model, which stands for optimal AP strategies.…”
Section: Theorem 3 Consider the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…The model of decision support system using hybrid method and actual weighting for … (M. Miftakul Amin) 2049 knowledge management based system that usually in mathematics model [15], and can be used to support decision taking in certain organization or company [16].…”
Section: Introductionmentioning
confidence: 99%
“…their research, Figueroa-Perez et al concluded that research tools used in marketing science contribute greatly to increasing the quality of the products created during product development and reduce the risk of market failure of the resulting product (Figueroa-Perez et al, 2019). …”
mentioning
confidence: 99%